2021
DOI: 10.5194/amt-2020-468
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

W-band Radar Observations for Fog Forecast Improvement: an Analysis of Model and Forward Operator Errors

Abstract: Abstract. The development of ground based cloud radars offers a new capability to continuously monitor the fog structure. Retrievals of fog microphysics is key for future process studies, data assimilation or model evaluation, and can be performed using a variational method. Both the one-dimensional variational retrieval method (1D-Var) or direct 3D/4D-Var data assimilation techniques rely on the combination of cloud radar measurements and a background profile weighted by their corresponding uncertainties to o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 16 publications
2
10
0
Order By: Relevance
“…A total of 31 fog events were observed over the period, the numbers of each type are detailed in table 3. In line with previous studies performed by (Philip et al, 2016;Dupont et al, 2016) and which looked at fog events in Paris, and Román-Cascón et al ( 2019), which examined fog events over a short period in January 2016 on the Spanish Northern Plateau, the majority of fog events were either cloud base lowering or radiative.…”
Section: Overview Of the Observed Fog Eventssupporting
confidence: 86%
See 4 more Smart Citations
“…A total of 31 fog events were observed over the period, the numbers of each type are detailed in table 3. In line with previous studies performed by (Philip et al, 2016;Dupont et al, 2016) and which looked at fog events in Paris, and Román-Cascón et al ( 2019), which examined fog events over a short period in January 2016 on the Spanish Northern Plateau, the majority of fog events were either cloud base lowering or radiative.…”
Section: Overview Of the Observed Fog Eventssupporting
confidence: 86%
“…Scores of FBI and CSI were found to be 1.59 and 0.32 respectively. The scores agree well with the work ofPhilip et al (2016) who calculated a score of 1.24 and 0.37 respectively as well asMartinet et al (2020) who found scores of 1.77 and 0.35. The FBI score indicates that the model over-predicts the occurrence of fog with a large number of false alarms and the CSI score means that only 32 % of fog events (observed and/or predicted) are correctly forecast by the model.…”
supporting
confidence: 90%
See 3 more Smart Citations